Pengujian performa Electric Ducted Fan (EDF) - Buyung Junaidin; Satya Wicaksono (ARMATUR : Artikel Teknik Mesin & Manufaktur, 2022)
EDF is an electric propulsion consists of a duct, fan, and electric motor with the motor power source coming from a battery which creates compression air for thrust. The design and configuration of an EDF is not complicated as a jet engine, but it could generate high thrust for highspeed flying like highspeed UAV needs. The preliminary design of an EDF yields a design and performance estimation. The design needs validation by experimental tests for real performance data. The test needs test tools and EDF itself. The aim of this research is experimental testing of an EDF for real performance data as validation of the existing design. The performance test is done by EDF test bed hence the manufacturing process of EDF is done by 3D printing. Test results show differences in performance of EDF with estimation results by analytical approach. The thrust of EDF from the experimental test is lower than the estimation calculation from the preliminary design, so the EDF does not fill the design criteria yet and needs refinement design.